como resolver estas equações irracionais?
A)
![\sqrt{x + 2} = \sqrt{2 \times + 2 } - 1 \sqrt{x + 2} = \sqrt{2 \times + 2 } - 1](https://tex.z-dn.net/?f=+%5Csqrt%7Bx+%2B+2%7D++%3D++%5Csqrt%7B2+%5Ctimes++%2B+2+%7D++-+1)
B)
![\sqrt{3x + 1} - \sqrt{ x + 4} = 1 \sqrt{3x + 1} - \sqrt{ x + 4} = 1](https://tex.z-dn.net/?f=+%5Csqrt%7B3x+%2B+1%7D++-++%5Csqrt%7B+x+%2B+4%7D++%3D+1)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
eleve as raizes ao ²
A)
x+2=2x+2-1
x+2=2x-1
x-2x=-1-2
-1x=-3
x=-3/-1
z=3
B)
3x+1-x+4=1
3x-x=1-4-1
2x=-4
x=-2
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Química,
1 ano atrás
Português,
1 ano atrás
Pedagogia,
1 ano atrás